(untitled) (Journal of Pathology of Nepal, 2015)
Background?Gastrointestinal cancer is the most common malignant tumor in China. This research aims to explore the association between HPV16-E6 protein and esophageal squamous cell carcinoma. Materials and Methods: SP immunohistochemical method was used to examine the expression of HPV 16-E6 in 50 cases of esophageal squamous cell carcinoma, 10 cases of normal esophageal squamous cell and 10 cases of adjacent tissue. Results: The expressions of HPV 16-E6 was significantly higher in esophageal carcinoma than in normal esophageal mucosa and in adjacent tissue. The expressions of HPV 16-E6 had correlation with invasive depth (P<0.05), but not with patient age, lymph node metastasis, tumor size (P>0.05). Conclusion: HPV 16-E6 can promote the growth and metastasis of esophageal squamous cell carcinoma and can be a prognostic factor of esophageal squamous cell carcinoma. Journal of Pathology of Nepal (2015) Vol. 5, 752-755